The complete mitochondrial genome of the Zig-zag eel Mastacembelus armatus (Teleostei, Mastacembelidae). (2nd January 2016) - Li, Qiang; Xu, Ruilin; Shu, Hu; Chen, Qian; Huang, Jianrong
Abstract: In this paper, the complete mitochondrial DNA (mtDNA) sequence of Mastacembelus armatus was determined. The mitochondrial genome is 16, 486 bp in length, including 13 protein-coding genes, 2 ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs) and a noncoding control region as those found in other vertebrates, with the gene identical to that of typical vertebrates. The overall base composition of the heavy strand are 25.28% of A, 29.13% of T, 14.65% of C and 30.93% of G, with a slight AT bias of 54.41%. With the exception of ND6 and eight tRNA genes, all other mitochondrial genes are encoded on the heavy strand.